Conductometric method development and validation to estimate acamprosate calcium in API and marketed formulation - Rahul K. Yadav, Meenaxi M. Maste, Shailendra S. Surywanshi, Utkarsh Shastri (Journal of Applied Pharmaceutical Science, 2021)
A simple, precise, rapid, low-cost conductometric method was developed and validated for the estimation of acamprosate calcium in pure and pharmaceutical formulation. The present research work utilized distilled water as a vehicle to prepare different concentrations of acamprosate calcium. The electrical conductivity of resulting solutions was measured by using an electrical conductometer ELICO CM 183EC-TDS analyzer version 2.3. The validation parameters were carried out according to the International Conference on Harmonization Guidelines. The developed method showed a linear response between concentration ranges of 50 and 250 µg/ml. The limit of detection and limit of quantification values were found to be 6.05 and 18.34 µg/ml, respectively. The relative standard deviation observed in precision, ruggedness, and robustness was in the acceptable range. The recovery of the proposed method was in the range of 98%–105%. The newly developed and validated conductometric method can be applied for the routine analysis of acamprosate calcium in pure and pharmaceutical formulation.
Keywords: Acamprosate calcium, alcohol dependence, electrical conductivity, ICH guidelines, quality control.